C–H Bond Functionalization of Amines: A Graphical Overview of Diverse Methods - Dutta, Subhradeep; Li, Bowen; Rickertsen, Dillon R. L.; Valles, Daniel A.; Seidel, Daniel (SynOpen, 2021)
This Graphical Review provides a concise overview of the manifold and mechanistically diverse methods that enable the functionalization of sp3 C–H bonds in amines and their derivatives.
Keywords: C–H bond functionalization; amines; heterocycles; catalysis; synthesis